Characteristics and mechanisms of liver injury caused by emerging infectious diseases - Cheng, Yi; Zheng, Xin (Frontiers in Immunology, 2025)
Abnormal liver function has become a common phenomenon in emerging infectious diseases caused by viruses, with incidence rates ranging from 2.5% to 98.6% across different pathogens. This review summarized the characteristics of liver injury caused by SARS-CoV-2, MERS-CoV, H7N9, SFTSV, DENV, and EBOV viruses. Viral infection initiates liver injury through direct attack, ischemia, and microthrombosis, triggering an exaggerated immune response often exacerbated by drug toxicity. Core mechanisms involve interconnected mitochondrial dysfunction (causing energy failure, ROS/mt-DNA release), endoplasmic reticulum stress (with dual roles in adaptation and apoptosis), and aberrant inflammation. These pathways form a vicious cycle, culminating in hepatocyte death, metabolic disruption, and severe hepatic damage. An in-depth exploration of the causes and mechanisms of liver injury also provides diversified strategies for treating and preventing these infectious diseases.